Effects of oxygen sources on properties of atomic-layer-deposited ferroelectric hafnium zirconium oxide thin films - Cho, Ah-Jin; Jeon, Ji Hoon; CHUNG, HONG KEUN; Baek, In hwan; Yang, Kun; Park, Min Hyuk; BAEK, SEUNG HYUB; Kim, Seong Keun (Pergamon Press Ltd., 2022)
Orthorhombic HfxZr1-xO2 (HZO) is a promising ferroelectric material for realizing ferroelectric devices in the modern semiconductor industry because of its excellent CMOS compatibility and scalability. Atomic layer deposition (ALD) facilitates the growth of robust ferroelectric HZO films that can be used in nanoelectronic devices. Herein, we provide a comprehensive understanding of the effects of the oxygen source, either H2O or O3, on the properties of ALD-grown HZO films. Although the growth per cycle promoted by ALD does not change with the type of oxygen source, the impurity content of the HZO film grown with H2O are higher than that with O3. The low impurity content of the HZO film grown with O3 results in low leakage current. The ALD process with O3 further suppresses the emergence of the nonferroelectric monoclinic phase in the ferroelectric orthorhombic HZO matrix. Consequently, the HZO film grown with O3 exhibits a small coercive field for ferroelectric domain switching and high electrical reliability. This study demonstrates that O3 is more favorable for growing high-quality HZO films via ALD by using metal precursors comprising tetrakis(ethylmethylamino) ligands.